2020
DOI: 10.1186/s12917-020-02617-8
|View full text |Cite
|
Sign up to set email alerts
|

Veterinarian barriers to knowledge translation (KT) within the context of swine infectious disease research: an international survey of swine veterinarians

Abstract: Background Food animal veterinarians face commodity specific and urgent global challenges yet conditions preventing use of best available knowledge have been sparsely studied. The American Association of Swine Veterinarians (AASV) membership (N = 1289) was surveyed online to benchmark their information priorities and their motivations and sources for keeping current with infectious disease research, and to describe their reported time, skill, access, and process as barriers to knowledge transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…We used three encoding strategies to encode the symbolic string sequences as input to ML algorithms: (1) dummy variable encoding was used to encode the categorical information into numeric values and (2) the increased dimensionality in the number of variables with low sample size makes ML algorithms prone to overfitting, which is also known as the 'curse of dimensionality' (38,39). As the ORF-5 sequences are highly dimensional, we reduced the dimensionality by using principal component analysis (PCA) based embedded representation for extracting low dimensional features of different sizes (i.e., 2,3,5,10,15,20). PCA selects the best-performing features which overcome the issues related to the 'curse of dimensionality. '…”
Section: Data Collection Data Cleaning and Data Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…We used three encoding strategies to encode the symbolic string sequences as input to ML algorithms: (1) dummy variable encoding was used to encode the categorical information into numeric values and (2) the increased dimensionality in the number of variables with low sample size makes ML algorithms prone to overfitting, which is also known as the 'curse of dimensionality' (38,39). As the ORF-5 sequences are highly dimensional, we reduced the dimensionality by using principal component analysis (PCA) based embedded representation for extracting low dimensional features of different sizes (i.e., 2,3,5,10,15,20). PCA selects the best-performing features which overcome the issues related to the 'curse of dimensionality. '…”
Section: Data Collection Data Cleaning and Data Preprocessingmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome (PRRS) is currently considered the most important endemic viral disease affecting commercial swine populations in North America ( 1 , 2 ). PRRS is present globally, with only a few countries with swine populations in Europe (i.e., Switzerland, Sweden, Norway, and Finland) and New Zealand free from it ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that approximately half of North American swine veterinarians interested in infectious disease research have access to 2 or fewer journals. 22 Some research may not be available to end users because of the language in which the report was written; this may be because English-speaking individuals cannot read non-English publications or because non-English-speaking individuals cannot read English publications. However, English is recognized as the lingua franca of scientific publications.…”
Section: Access To Research Reportsmentioning
confidence: 99%
“…In 1990, the Institute of Medicine (IOM) of the National Academy of Sciences defined Clinical Practice Guidelines (CPGs) as "systematically developed recommendations to help clinicians and patients make important decisions about patient care for certain clinical conditions" [14,15]. The IOM guidelines advisory panels created clear standards for appraising the appropriateness of practice guidelines.…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%